Managing Investment Climate Reforms: The Peru Urban Land Reform Case Study - Endo, Victor (Washington, DC: World Bank, 2012)
The urban land policy reforms implemented in Peru since 1996 aimed at the creation of a system able to assure formal rights to real property in large urban settlements. This case study looks at the factors that motivated reform, how the reform process itself was managed, the results, and lessons learned.